2004
DOI: 10.2170/jjphysiol.54.295
|View full text |Cite
|
Sign up to set email alerts
|

Determination In Vivo of Newly Synthesized Gene Expression in Hamsters During Phases of the Hibernation Cycle

Abstract: Hibernation is a circannual adaptation and within the hibernation season, the hibernation cycle of a 'classic' hibernator, such as the Syrian hamster, can be divided into six distinct physiological phases. An entrance phase, when metabolism is inhibited and body temperature decreases [1]. A long period of torpor when metabolic rate (MR) is approximately 2.5% of resting metabolic rate (RMR) [2, 3]. This is followed by an arousal period of three phases: an early arousal phase during which the animal warms anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…For example, the rate of [ 3 H]-uridine incorporation into RNA was reduced by 8-fold in brain of torpid ground squirrels compared with euthermic animals (Bocharova et al, 1992). A similar result was seen when [ 3 H]-uridine incorporation into RNA was measured in multiple organs of hibernating Syrian hamsters (Mesocricetus auratus) (Osborne et al, 2004) and was also indicated from nuclear run-on assays performed on liver extracts of golden-mantled ground squirrels (van Breukelen and Martin, 2002). A reduction in energetically-costly transcription was also seen in Djungarian hamsters (Phodopus sungorus) undergoing daily torpor bouts (Berriel Diaz et al, 2004).…”
Section: Metabolic Suppression In Hibernationmentioning
confidence: 52%
See 1 more Smart Citation
“…For example, the rate of [ 3 H]-uridine incorporation into RNA was reduced by 8-fold in brain of torpid ground squirrels compared with euthermic animals (Bocharova et al, 1992). A similar result was seen when [ 3 H]-uridine incorporation into RNA was measured in multiple organs of hibernating Syrian hamsters (Mesocricetus auratus) (Osborne et al, 2004) and was also indicated from nuclear run-on assays performed on liver extracts of golden-mantled ground squirrels (van Breukelen and Martin, 2002). A reduction in energetically-costly transcription was also seen in Djungarian hamsters (Phodopus sungorus) undergoing daily torpor bouts (Berriel Diaz et al, 2004).…”
Section: Metabolic Suppression In Hibernationmentioning
confidence: 52%
“…For example, plasma membrane Na + K + -ATPase activity was reduced by 60% during hibernation (MacDonald and Storey, 1999) and the activity of sarco(endo)plasmic reticulum Ca 2+ -ATPase as well as the levels of other proteins associated with calcium signaling were similarly reduced (Malysheva et al, 2001). Strong overall suppression of ATP-expensive protein synthesis has also been confirmed in hibernators in both in vivo and in vitro studies that monitored 14 C-leucine or 3 H-leucine incorporation into proteins (Frerichs et al, 1998;Hittel and Storey, 2002;Osborne et al, 2004). Finally, the overall rates of gene transcription are also greatly reduced during deep torpor bouts in hibernators.…”
Section: Metabolic Suppression In Hibernationmentioning
confidence: 85%
“…Use of nuclear run-on assays from liver allowed for mechanistic insight into how this transcriptional depression is effected; overall, transcriptional initiation is reduced by ~50% during torpor, but the cold temperatures typical of hibernation would essentially arrest elongation (van Breukelen and Martin, 2002). Data from nuclear run-on assays in hibernating hamsters are consistent with a significant role for depression of elongation as well (Osborne et al, 2004; Berriel Diaz et al, 2004). One might expect that employment of a hibernation phenotype, with the associated reduction in metabolism, might be accompanied by dramatic changes in gene expression.…”
Section: Discussionmentioning
confidence: 86%
“…Because organs such as the heart and brain must function during torpor, it seems likely that these tissues would experience higher transcriptional activities than tissues such as muscle. Indeed, such differences have been noted (Osborne et al, 2004). Use of nuclear run-on assays from liver allowed for mechanistic insight into how this transcriptional depression is effected; overall, transcriptional initiation is reduced by ~50% during torpor, but the cold temperatures typical of hibernation would essentially arrest elongation (van Breukelen and Martin, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation